2014
DOI: 10.1111/pme.12248
|View full text |Cite
|
Sign up to set email alerts
|

Do Low Levels of Beta-Endorphin in the Cerebrospinal Fluid Indicate Defective Top-Down Inhibition in Patients with Chronic Neuropathic Pain? A Cross-Sectional, Comparative Study

Abstract: Patients with chronic neuropathic pain due to trauma or surgery had low levels of beta-endorphin in the CSF. We speculate that this could indicate a defective top-down modulation of pain in chronic neuropathic pain. Our results also illustrate the importance of taking a system-wide, multivariate approach when searching for biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…There may of course be some false positives among our findings, but all in all it does not seem sensible to dismiss all our results as a gigantic type I error. The MVDA methodology used in the present study is the same as used by the Linköping group in a number of recent peer-reviewed publications in different journals,22,29,6266 and it is congruent with the principles argued for by Wheelock and Wheelock 28. Finally, in order to ensure the robustness of our statistical methodology, the CSF data of the present study were recomputed using the statistical methodology described by Moen et al32 (with use of false discovery rate); the result of this recomputation was exactly the same as the list presented in Table 1 (TG being the last author of both articles).…”
Section: Discussionmentioning
confidence: 99%
“…There may of course be some false positives among our findings, but all in all it does not seem sensible to dismiss all our results as a gigantic type I error. The MVDA methodology used in the present study is the same as used by the Linköping group in a number of recent peer-reviewed publications in different journals,22,29,6266 and it is congruent with the principles argued for by Wheelock and Wheelock 28. Finally, in order to ensure the robustness of our statistical methodology, the CSF data of the present study were recomputed using the statistical methodology described by Moen et al32 (with use of false discovery rate); the result of this recomputation was exactly the same as the list presented in Table 1 (TG being the last author of both articles).…”
Section: Discussionmentioning
confidence: 99%
“…Bäckryd et al, found no significant correlation between CSF b endorphin level and use of pain medications in patients with chronic neuropathic pain [9]. However, Tramadol which is a drug with mild opiate properties had evidence from randomized controlled trials showing that tramadol is an effective treatment for neuropathic pain [33].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that CSF-levels of b-endorphin are not a reflection of its peripheral levels [34]. Also Bäckryd et al, reported that there are probably two functionally different b-endorphin systems: one peripheral (release of b-endorphin by the pituitary into the systemic circulation) and one central (synthesis in hypothalamic pro-opio-melanocortin (POMC) neurons) [9], with an intact blood-brain barrier (BBB) hinders free exchange of b-endorphin between plasma and CSF [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma substance P and β-endorphin were not quantified at the site of stimulation. Also recognize that central versus circulating neuropeptides represent functionally different systems (2,3,14,59). For example, CNS β- endorphin release can also reduce pain via GABAergic inhibition.…”
Section: Strengths and Limitationsmentioning
confidence: 99%